2023
DOI: 10.1161/circulationaha.121.058767
|View full text |Cite|
|
Sign up to set email alerts
|

A Human Hereditary Cardiomyopathy Shares a Genetic Substrate With Bicuspid Aortic Valve

Abstract: BACKGROUND: The complex genetics underlying human cardiac disease is evidenced by its heterogenous manifestation, multigenic basis, and sporadic occurrence. These features have hampered disease modeling and mechanistic understanding. Here, we show that 2 structural cardiac diseases, left ventricular noncompaction (LVNC) and bicuspid aortic valve, can be caused by a set of inherited heterozygous gene mutations affecting the NOTCH ligand regulator MIB1 (MINDBOMB1) and cosegregating genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 116 publications
0
14
0
Order By: Relevance
“…Our data are in full agreement with the results of a report showing that double heterozygous Mib1 V943F/+ ; Notch1 +/− mice show highly significant BAV. 37 Previously, our group and others demonstrated that deleterious MIB1 variants associated with LVNC, 40,53 atrial septal defects and VSDs, and patent ductus arteriosus. 54 A complex phenotype of BAV and cardiac muscle malformation, as found in 1 case in the discovery cohort, has also been described.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our data are in full agreement with the results of a report showing that double heterozygous Mib1 V943F/+ ; Notch1 +/− mice show highly significant BAV. 37 Previously, our group and others demonstrated that deleterious MIB1 variants associated with LVNC, 40,53 atrial septal defects and VSDs, and patent ductus arteriosus. 54 A complex phenotype of BAV and cardiac muscle malformation, as found in 1 case in the discovery cohort, has also been described.…”
Section: Discussionmentioning
confidence: 95%
“…We have described recently the generation of the mice harboring the Mib1 V943F variant. 37 Mice heterozygous for Notch 38 (denoted as Notch1 +/− ) and Rbp 39 (denoted as Rbp +/− ) variant lines were used for genetic sensitization studies with Mib1 alleles.…”
Section: Generation Of Mib1 K735r Mouse Linementioning
confidence: 99%
See 1 more Smart Citation
“…Jagged1 (Jag1) signaling is dispensable for this process, but the later remodeling of the valve primordia requires induction of Notch activity by Jag1 expressed on endocardial cells 6 . Dysregulation of NOTCH signaling is associated with human valvular congenital heart disease (CHD) 7,8,9,10,11 and acquired calcific aortic valve disease (CAVD) 12,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Without exception, these proteins do not exist in yeast, and only participate in the metazoan complexes. The molecular function of most accessory subunits and their role within mSWI/SNF remain incompletely defined 8,9,10,11,12,13,14 . It has been reported that BCL7 proteins accumulate at sites of DNA damage, but the role they may play in DNA damage repair (DDR) is unknown 15 .…”
Section: Introductionmentioning
confidence: 99%